ETIKA PROFESI DAN PROFESIONALISME - Pane, Endi Hadian Shabar; Muhaini, Muhaini; Pangestu, Wira Yoga; Afifah, Nur; Hutagalung, Zulkarnain (Jurnal Ilmiah Wahana Pendidikan, 2024)
Ethics in the profession is an essential foundation that regulates the behavior, responsibilities and actions of a professional. This article focuses on the close relationship between professional ethics and the concept of professionalism in a broader context. Explaining the definition, concept, and importance of professional ethics, this article also explores the main aspects of the code of ethics which serve as guidelines for professional behavior. An in-depth analysis of how professional ethics provides the basis for social responsibility and its impact on the performance and reputation of the profession is also presented. In addition, this article highlights the complexity in implementing and monitoring codes of ethics in various professions, and reviews the role of professional ethics in forming a strong professionalism paradigm in various work domains. By focusing on its relationship to the concept of professionalism, this article summarizes efforts to develop professional ethics as an important pillar in building and maintaining quality and integrity in the world of work.​